RANCANG BANGUN SISTEM INFORMASI PENJUALAN JASA PENITIPAN BAGASI DI BANDARA PADA LOCKER AIRPORT INDONESIA - Anggara Wijaya, I Nyoman Yudi; Adi Mega Putra, Anak Agung Gede; Kamajaya, Vira Adhi (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2024)
In the aviation industry, baggage storage or locker services at airports are crucial aspects that require efficient and coordinated management. Locker Airport Indonesia handles an average of 30 baggage storage transactions daily. However, the main issue faced by Locker Airport Indonesia is the lack of an informative online system to manage detailed records of stored baggage and the accumulation of unorganized paper reports. The complex manual administration process takes approximately 15 minutes to complete one baggage storage transaction. This study involves the design and development of a web-based baggage storage sales information system at Locker Airport Indonesia using the SDLC (System Development Life Cycle) method with the Waterfall model. This structured approach begins with a needs analysis, followed by implementation and testing. The system evaluation was conducted using the EUCS (End User Computing Satisfaction) method, which measures five key dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. The Likert scale evaluation results show that user satisfaction levels fall into the "Satisfied" category in all dimensions, with an average score of 4, indicating high satisfaction in each dimension. Thus, the development of this web-based information system has successfully provided numerous benefits and met user expectations.